In the current global economic climate, what are the factors that will affect the ringgit exchange rate - Chia, Jing Ying; Kong, Weng Yan; Lau, Yen Shan; Liew, Kai Jun (2023)
This study aims to determine the factors that affect Malaysian Ringgit against U.S. Dollar in current world in long run and short run namely interest rate, inflation rate, hot money and stock market return. The data used in this study is secondary data while 55 observations are being obtained in quarterly manner, covering from Q1 2009 to Q3 2022. The data is being derived from different sources like World Bank database, Bank Negara Malaysia, Ceic database, Yahoo Finance, and Department of Statistic Malaysia (DOSM). Furthermore, data is analyzed by using Eviews version 12. The tests carried out in this study include unit root test, long run relationship, short run dynamics and diagnostic checking. The results showed that only hot money and stock market return have long-run significant relationship with Malaysian Ringgit against U.S. Dollar while the others are insignificant. In addition, the result of this study is inconsistent with some previous studies because the data used by our study might be different with the previous study. However, there are also a few previous studies stated that the exchange rate of different country should be determined with different factors, therefore the results might be ambiguous sometimes. For instance, some previous studies took inflation rate differential to conduct the study but this study is using CPI for the inflation rate factor. In addition, some limitations had been determined in this study such as limited data available and other potential factor can be used by this study while there are also recommendations had been suggested for the potential readers on the future studies.